Thyrotoxic periodic paralysis mimicking hypokalemic periodic paralysis - Vivek Chaudhari, Dr.; Harshvardhansinh Chauhan, Dr.; Manisha Panchal, Dr. (International Journal of Medicine, 2022)
Thyrotoxic periodic paralysis is a unique disorder that causes episodic proximal lower extremity muscle weakness in a patient who already has a hyperthyroid state and is not treated for the underlying disease state. The affected population mostly includes Asian in origin specifically the male gender (vs most thyroid disorder affects the women gender). Precipitating factors include in addition to a hyperthyroid state are strenuous exertion, a high-carbohydrate meal, and drugs like diuretics, insulin, high dose of steroids, antiretrovirals, and interferon therapy. Other genetic causes include the decreased activity of Kir2.6 mutation increased activity of Na+/K+ ATPase causing an intracellular shift of potassium that leads to hypokalaemia. The other challenging part for the physician is to differentiate it from Familial periodic paralysis an autosomal disorder seen in Caucasians and Western countries because both the disorders present similarly and differentiate between them by the presence of hyperthyroid state with hypokalaemia in Thyrotoxic periodic paralysis. The mortality is associated with respiratory paralysis hence the acute intervention includes giving nonselective beta-blockers followed by anti-thyroid medications. We present a case of an Indian adolescent who presented to us with lower muscle weakness with an underlying thyrotoxicosis state. This help physician with early diagnosis and appropriate treatment.Â Â Â